Computer support for Competitive Intelligence - Bartuś, Kamila (Komputerowe wspomaganie Competitive Intelligence, 2021)
The main aim of the article is to present a theoretically well-grounded discussion on Competitive Intelligence and its computing support. This article is an attempt to answer the following questions: (1) What is the idea of Competitive Intelligence and its computer support? (2) How to use the Competition Profile Matrix (CPM), Business Model Canvas (BMC), Resource Based View (RBV) and Industrial Organization (IO) in competition analysis? (3) What are their advantages for Computer Aided CI? The search for answers to these questions was conducted mainly on the basis of theoretical and empirical research.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 2 (60), s. 1-13
Keywords: Competitive Intelligence; Competitive Profile Matrix; business model canvas; Resource Based View; industrial organization